'A true partner around the table?' Perceptions of how to strengthen public health's contributions to the alcohol licensing process. (1st June 2018) - Reynolds, Joanna; McGrath, Michael; Engen, Jessica; Pashmi, Ghazaleh; Andrews, Matthew; Sharpe, Carolyn; Egan, Matt; Lim, Jin; Lock, Karen
Abstract: Introduction: There are increased opportunities for public health practitioners (PHPs) in England to shape alcohol availability and reduce harms through a statutory role in licensing processes in local government. However, how public health can effectively influence alcohol licence decision-making is little understood. Methods: A mixed methods study was conducted to identify challenges faced by PHPs and mechanisms to strengthen their role. This involved a survey of practitioners across London local authorities ( n = 18) and four focus group discussions with a range of licensing stakeholders ( n = 36). Results: Survey results indicated a varied picture of workload, capacity to respond to licence applications and levels of influence over decision-making among PHPs in London. Practitioners described a felt lack of status within the licence process, and difficulties using and communicating public health evidence effectively, without a health licensing objective. Strategies considered supportive included engaging with other responsible authorities and developing understanding and relationships over time. Conclusions: Against political and resource constraints at local and national government levels, pragmatic approaches for strengthening public health influence over alcohol licensing are required, including promoting relationships between stakeholders and offering opportunities for PHPs to share best practice about making effective contributions to licensing.